Hambatan Bidan dalam Memberikan Pelayanan Persalinan di Praktik Mandiri Bidan (PMB) Pada Masa Pandemi Covid-19 - Siti Zakiah Zulfa; Linda Suryani (STIKes Payung Negeri Pekanbaru, 2023)
The emergence of a new virus called Coronavirus Disease 2019 (COVID-19) at the end of December 2019 had an extraordinary impact on all aspects of life, especially in the world of health. Health workers such as midwives in Independent Midwife Practices (PMB) must adapt delivery services to the conditions of the COVID-19 pandemic and often encounter barriers in their implementation. This study aimed to explore in depth the barriers by midwives in providing delivery services at PMB during the COVID-19 pandemic. This study uses a qualitative descriptive study through a phenomenological approach, involving ten informants. Data collection was carried out using one-on-one in-depth online interviews with a semi-structured interview guide. Data analysis was done manually using thematic analysis. The results of the data analysis show that midwives encountered barriers while providing delivery services at PMB during the COVID-19 pandemic, including; difficulties in obtaining Personal Protective Equipment (PPE) at the beginning of the pandemic, patient non-compliance in implementing health protocols, midwives infected with COVID-19, and a referral system that did not work well.